A revealing look at medical students' performing in their first clinical year: what does it mean for the long case? - Sim, J.H.; Daniel, E.S.G. (2014)

(untitled)
ln the University of Malaya, first clinical year (Year 3) Exam consists of 4 components. Component A is Continuous Assessment (CA). Components B (Theory), C (Long Case) and D (OSCE) are components of the final exam. The purpose of this study was to examine medical students' performance in Year 3 Exam. The objectives were: (i) to explore possible relationships between (a) students' overall performance and their performance in each of the 4 exam components, (b) students' performance in CA and their performance in each component in the finals, (c) students' performance in Component B and Components C and D, and (ii) to conduct further analysis on the performance of students who failed the exam.